Efforts to Improve the Performance of Precision Pioneer Patrols by the Madiun Police Samapta Unit in the Prevention of the Crime of Theft - Akbar, Rizky (Advances in Police Science Research Journal, 2024)
The increase in the number of motor vehicle theft crimes in the jurisdiction of Madiun Regency has caused unrest for the local community. Indonesian National Police responded to this by taking precautions by the Samapta Unit of the Madiun Police Resort. This study aims to identify performance improvement efforts by the Samapta Unit of the Madiun Police Resort in preventing motor vehicle theft. This research uses qualitative approach and ethnographic research method. Data collection is carried out by conducting interviews, observations, and document studies. For data analysis techniques used, namely data collection, data reduction, data presentation, and conclusions. This research uses conceptual literature including: the concept of effort, the concept of samapta unit, the concept of Perintis Presisi Patrol, the concept of motor vehicle theft, management theory, performance theory, hotspot policing theory, and routine activity theory. The factual condition in this study is that the implementation of the Perintis Presisi Patrol by the Samapta Unit of the Madiun Police Resort in preventing motor vehicle theft is still insufficient because obstacles are still found in the implementation of the Perintis Presisi Patrol, including incomplete equipment owned, ineffective patrol targeting, lack of personnel, absence of personnel backup, implementation of patrols on the route and beat that are always the same, and the determination of patrol targets that have not been in accordance with the development of curanmor crimes. In addition, the performance of members of the Samapta Unit of the Madiun Police Resort still experiences constraints on the ability of personnel who are not yet appropriate, lack of fuel budget, low work motivation, and have not established cooperation with other agencies. The conclusion of this study is that efforts to improve the performance of Perintis Presisi Patrol by the Samapta Unit of the Madiun Police Resort in preventing motor vehicle theft already exist but are not yet significant. Likewise, the implementation of Perintis Presisi Patrol in preventing motor vehicle theft has not yet reached the key to success and has not received optimal results.